2015
DOI: 10.1002/jso.24111
|View full text |Cite
|
Sign up to set email alerts
|

The importance of surgical margins in melanoma

Abstract: Optimization of margins to minimize morbidity and maximize local control is critical to the success of surgical management of primary melanomas. This article synthesizes the historical perspectives and key clinical trials that have contributed to the evolution of resection margins for melanoma, focusing on the importance of surgical margins in the context of an era of improvements in systemic therapy and greater use of minimally invasive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 90 publications
3
26
0
2
Order By: Relevance
“…For large melanoma, in situ surgical margins >0.5 cm may be necessary to achieve histologically negative margins. A 0.5-cm margin for lentigo maligna melanoma in situ on the head and neck often results in an incomplete excision (4). This is often managed as a staged procedure, where histological clearance is confirmed prior to definitive reconstruction.…”
Section: Review Of Current Guidelines For Excisionmentioning
confidence: 99%
“…For large melanoma, in situ surgical margins >0.5 cm may be necessary to achieve histologically negative margins. A 0.5-cm margin for lentigo maligna melanoma in situ on the head and neck often results in an incomplete excision (4). This is often managed as a staged procedure, where histological clearance is confirmed prior to definitive reconstruction.…”
Section: Review Of Current Guidelines For Excisionmentioning
confidence: 99%
“…Guidelines for the treatment of melanoma now specifically acknowledge differences in treatment based on anatomic location. 5,6 There is a paucity of evidence to guide decision-making for conventional excision of AIMP; expert dermatopathologists were unable to reach consensus regarding recommended margins for AIMP. 2 The lack of clinical evidence to guide decision-making in the surgical management of AIMP presents a dilemma for treating clinicians, and objective data are necessary to help fill this knowledge gap.…”
mentioning
confidence: 99%
“…While margins as wide as 5 cm were once commonplace, current guidelines from the National Comprehensive Cancer Network (NCCN), the European Society for Medical Oncology (ESMO), the Swiss Cancer League, and the Australian Cancer Network all recommend margins no greater than 2 cm. 5 Shifting to narrower excision margins represents a potential challenge to physicians who have experienced good oncological outcomes with wider margins. This inertia of prior experience may explain why nearly half of the excisions performed in this study had wider margins than recommended, and why Varey et al 2 found physicians aged 55-64 years were 32% less likely to adhere to guidelines compared with those aged under 45 years.…”
Section: Physician Behaviormentioning
confidence: 99%